Unusual case of nephrocutaneous fistula – Our experience - Rajeev Thekumpadam Puthenveetil; Debajit Baishya; Sasanka Barua; Debanga Sarma (Asian Journal of Urology)
A rare case of nephrococutaneous fistula due to spontaneous expulsion of renal calculi is described. A 45-year-old man presented with urinary leakage from an ulcer over the left lumbar region for the last 3 months after a history of spontaneous expulsion of stones from this area. Ultrasonography abdomen revealed a small contracted kidney with multiple calculi in the kidney and renal pelvis, sinus tract from the lower pole of the left kidney with a ruptured calyceal calculus in the sinus tract. CT urography revealed a non excreting left kidney with multiple renal calculi, with hyperdense collection in the renal parenchyma extending to the subcutaneous tissue and left lung suggesting a xenthogranulomatous pyelonephritis (XGP). We performed a left-sided simple nephrectomy with excision of the fistulous tract. Histopathological examination revealed XGP. There have been a few case reports of XGP forming nephrocutaneous fistula in the back.